2018
DOI: 10.1002/bkcs.11383
|View full text |Cite
|
Sign up to set email alerts
|

Study on Anti‐Proliferative Activity in Cancer Cells and Preliminary Structure–Activity Relationship of Pseudo‐Peptide Chiral Thioureas

Abstract: In our previous studies, we have shown that thiourea compounds containing phosphate esters have potent antitumor activity and can be used as a novel strategy for the development of antitumor agents. Herein, a series of novel phosphonate thioureas 5–38 have been synthesized, which were fully characterized by 1H NMR, 13C NMR spectrum, elemental analysis. Three human cancer cell lines (Bcap‐37, BGC‐823, and PC‐3) have been used to investigate these compounds’ antitumor activities. After the summarization of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These peptides exhibited promising antiproliferative activity against several cancer cell lines (BCG-823, A-549, PC-3, Bcap-37 and BCG-823) with compounds 25, 26, 27 and 28 being the most active. 44,45 An addition of diethyl or dimethyl phosphites to aldehydes derived from S-phenylalanyl-S-alanine resulted in diastereomeric mixtures of dipeptidyl 2-amino-1-hydroxyphosphonates (Fig. 8).…”
Section: B Peptides Containing C-terminal Aminophosphonic Acidsmentioning
confidence: 99%
“…These peptides exhibited promising antiproliferative activity against several cancer cell lines (BCG-823, A-549, PC-3, Bcap-37 and BCG-823) with compounds 25, 26, 27 and 28 being the most active. 44,45 An addition of diethyl or dimethyl phosphites to aldehydes derived from S-phenylalanyl-S-alanine resulted in diastereomeric mixtures of dipeptidyl 2-amino-1-hydroxyphosphonates (Fig. 8).…”
Section: B Peptides Containing C-terminal Aminophosphonic Acidsmentioning
confidence: 99%
“…Thioureas show promise as anticancer drug candidates due to their sulfur atoms, with sulfur itself being a versatile and biologically important element to all living organisms . Thiourea derivatives have been synthesised with an assortment of partnering organic structures and demonstrated to exert anti‐cancer effects in human cancer cell lines from different entities including breast and lung cancer as well as leukaemia …”
Section: Methodsmentioning
confidence: 99%
“…[24] Thiourea derivatives have been synthesised with an assortment of partnering organic structures and demonstrated to exert anti-cancer effects in human cancer cell lines from different entities including breast and lung cancer as well as leukaemia. [25][26][27]28] We are currently investigating guanidine-and thioureabased molecules as components in advanced organic LED materials through formation of luminescent iridium complexes. [29,30] Iridium complexes themselves are of great interest as potential cancer therapeutics because they generate a 3D scaffold, enabling structural diversity beyond the 'flatter' organic molecules or platinum complexes used in cancer therapy; they offer an opportunity for simultaneous imaging due to their rich and tunable luminescence properties; [31] and they offer an opportunity for photogeneration of singlet oxygen within cells.…”
mentioning
confidence: 99%
“…The compounds containing fluorine groups in the amino acid amide structure showed significant anticancer activity. Authors concluded that the variation of alkyl groups in the novel phosphonate thioureas contribute to their anticancer activity [ 193 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%